Siblings, not triplets: social preferences for risk, inequality and time in discounting climate change - Giles D. Atkinson; Simon Dietz; Jennifer Helgeson; Cameron Hepburn; Håkon Sælen (Kiel Institute for the World Economy (IfW), 2009)
Arguments about the appropriate discount rate often start by assuming a Utilitarian social welfare function with isoelastic utility, in which the consumption discount rate is a function of the (constant) elasticity of marginal utility along with the (much discussed) utility discount rate. In this model, the elasticity of marginal utility simultaneously reflects preferences for intertemporal substitution, aversion to risk, and aversion to (spatial) inequality. While these three concepts are necessarily identical in the standard model, this need not be so: well-known models already enable risk to be separated from intertemporal substitution. Separating the three concepts might have important implications for the appropriate discount rate, and hence also for long-term policy. This paper investigates these issues in the context of climate-change economics, by surveying the attitudes of over 3000 people to risk, income inequality over space and income inequality over time. The results suggest that individuals do not see the three concepts as identical, and indeed that preferences over risk, inequality and time are only weakly correlated. As such, relying on empirical evidence of risk or inequality preferences may not necessarily be an appropriate guide to specifying the elasticity of intertemporal substitution.
Keywords: Q51; C90; D01; D63; 330; Climate change; discounting; risk aversion; intertemporal substitution; inequality aversion; intergenerational equity; Klimaveränderung; Soziale Diskontrate; Risikoaversion; Zeitpräferenz; Verteilungsgerechtigkeit; Generationenbeziehungen; Meinung; Feldforschung; Welt